Malady in the sky - Abdul Razak, Mariatulqabtiah; Omar, Abdul Rahman; Abdul Razak, Rabeah Adawiyah (Universiti Putra Malaysia Press, 2015)
Birds migrating across national and intercontinental borders can play a role in the spread of infectious diseases. Their capability to travel over long distances and through a diversity of habitats exposes them to a wide range of microorganisms such as bacteria, virus, parasite or drug-resistant organisms. Similar to wild birds, these migratory birds are hosts or natural reservoirs for many zoonotic diseases. Without showing any clinical signs, they act as a silent disease carrier by possessing pathogens that can threaten the well-being of other animals and humans, hence, raising concern on public confidence in health care, food safety, and security.